Expectations and Sensation-Seeking as predictors of Binge Drinking in adolescents - Pérez-Fuentes, María del Carmen; Molero, María del Mar; Gázquez Linares, José Jesús (Anales de Psicología / Annals of Psychology, 2018)
The different current modalities of alcohol use in adolescents include episodes of binge drinking. The objective of this study was to analyze the variables involved in starting and continuing binge drinking, and the predictor roles of sensation-seeking and expectations about alcohol in excessive drinking and the intention of continuing this practice in the medium-to-long term. A sample of 315 high school students answered a series of questions related to drinking alcohol. They were also given standardized tests including the Alcohol Expectancy Questionnaire-Adolescent, Brief and the Sensation-Seeking Scale to evaluate their expectations about alcohol and their tendency towards sensation-seeking. The results show that the tendency towards sensation-seeking plays a determining function in the involvement of adolescents in risky behavior, while positive expectations about the results of drinking minimize apparent risks and make it easier to acquire and maintain alcohol drinking habits. We highlight the importance of expanding research into the different types of adolescent drinking and applying the research to the design of effective drinking prevention interventions.